2012
DOI: 10.1177/03946320120250s104
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type a in Cervical Dystonia

Abstract: Cervical dystonia is a syndrome characterized by anomalous postures and unintentional repetitive movements of the head and the neck. Aim of this study is to show the effectiveness of the combined treatment botulinum toxin-FKT through the use of a recent methodic of investigation, myoton, and of the classical clinical evaluations, such as Tsui and VASscales. 15 patients (9 females, 6 males) have been selected. During the initial visit and in the following controls, performed every month, patients have been subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Muscle tension and stiffness values decreased at four weeks after BoNT injections, and elasticity values increased at eight weeks after BoNT injections. The results of the present study are somewhat similar to the results reported by Marvulli et al [ 8 ], who combined BoNT injections and physiotherapy for the treatment of CD in 15 patients. They performed clinical evaluation and myotonometric measurements using the Myoton-3 before and at one, two, and three months following BoNT injections.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Muscle tension and stiffness values decreased at four weeks after BoNT injections, and elasticity values increased at eight weeks after BoNT injections. The results of the present study are somewhat similar to the results reported by Marvulli et al [ 8 ], who combined BoNT injections and physiotherapy for the treatment of CD in 15 patients. They performed clinical evaluation and myotonometric measurements using the Myoton-3 before and at one, two, and three months following BoNT injections.…”
Section: Discussionsupporting
confidence: 92%
“…However, the differences in study designs between that study and the present study may partly explain the differences in results. Patients in the present study had been receiving BoNT injections for years, whereas patients in the study of Marvulli et al [ 8 ] received their first BoNT injections. It has been reported that long-term use of BoNT results in a decrease in contractile tissue and an increase in connective tissue [ 15 ], thus making the muscle more rigid.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Botulinum toxin is the first-choice treatment for focal dystonia. 10,36,37 Some studies have showed improvement of dystonia with the use of levodopa in both, ATLD and AT. 20,38 Oral drugs therapy with anticholinergic drugs (eg biperiden and trihexyphenidyl) 10,37 and GABA (c-aminobutyric acid) mimetics (eg baclofen, clonazepam) may alleviate symptoms in patients with generalized dystonia, blepharospasm, pain and oromandibular dystonia.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Some drugs may be useful in the management of symptoms. Botulinum toxin is the first‐choice treatment for focal dystonia 10,36,37 . Some studies have showed improvement of dystonia with the use of levodopa in both, ATLD and AT 20,38 .…”
Section: Literature Reviewmentioning
confidence: 99%